Percepcja wykorzystania technologii deepfake w materiałach wideo wśród studentów - Proszowska, Klaudia (Wydawnictwa AGH, 2024)
This research focuses on public opinion regarding the use of deepfake technology in video materials"," materials considered particularly dangerous in terms of fake content dissemination. It studies how students understand and evaluate deepfakes and their opinion regarding harmfulness of deepfakes at three levels: at the level of society, for the person presented in the material and for the viewer. The research investigates also whether deepfakes shall be clearly marked as fake. Deepfakes were considered in five categories: as an art project, a satire, propaganda material, fake news or a pornographic material. The link to the user’s proximity to technology was also explored. Generally, the attitude towards deepfakes was rather negative, with pornographic materials seen as the most harmful, and artistic projects – as the least. Regardless of the category, most respondents were in favor of clear labels on deepfake materials. Proximity to technology does not have a direct impact on the declared attitudes, although people closest to technology consider pornographic deepfake materials as less harmful, and general deepfake technology to be slightly more interesting and relevant in the future.

Niniejszy artykuł skupia się na opiniach dotyczących wykorzystania technologii deepfake w materiałach wideo uznawanych za szczególnie niebezpieczne w kontekście rozpowszechniania fałszywych treści. Badanie pomogło określić, jak studenci rozumieją i oceniają deepfaki oraz jak ich opinia dotycząca szkodliwości (na poziomie społeczeństwa, osoby przedstawionej w materiale oraz osoby oglądającej) i konieczności oznaczenia fałszywości materiału zależy od wyróżnionych pięciu kategorii deepfake’ów: projektu artystycznego, satyry, materiału propagandowego, fake newsa oraz materiału pornograficznego. Sprawdzono również, czy te opinie są zależne od stopnia znajomości technologii. Badanie pokazało ogólnie negatywny stosunek do deepfake’ów, a za najbardziej szkodliwe na wszystkich płaszczyznach uznaje się materiały pornograficzne, projekty artystyczne z kolei – za najmniej szkodliwe. Pomimo nieznacznych różnic między kategoriami materiałów deepfake respondenci opowiadali się zwykle za ich czytelnym oznaczaniem. Znajomość technologii raczej nie ma bezpośredniego wpływu na postawy ankietowanych, chociaż osoby deklarujące jej lepszą znajomość uważają deepfaki za nieco bardziej przyszłościowe i interesujące, a materiały pornograficzne za mniej szkodliwe.
The perception of deepfake technology in video materials among university students